Interim PET for prognosis in adults with Hodgkin lymphoma: A prognostic factor exemplar review - Skoetz, N; Collins, G; Moons, K; Estcourt, L; Engert, A; Kobe, C; von Tresckow, B; Trivella, M (Wiley, 2017)
This is a protocol for a Cochrane Review (Prognosis). The objectives are as follows: Primary objective: The objective of this systematic review is to identify all studies evaluating interim PET scan results as a prognostic factor, describe the characteristics and risk of bias of included studies and if possible, meta-analyse results on the association between PET scan results and overall or progression-free survival and adverse events.